Promotion Related Preferences of News Channel Audiences in Indore and Dehradun-A Comparative Study - Sapre, Anand; Nagpal, Amit (Indian Journal of Marketing, 2009)
Promotion is one of the critical elements of marketing mix of a news channel. Promotion (broadcast) refers to a channel's efforts to promote itself to advertisers (for revenue) and audience (for revenues and getting high TRPs). Promotion can be on air or off air. Promotion includes advertisements, public relations, sales promotion, publicity, and events. A network/channel informs its audiences of new channel/programs, events, change in time schedules and so on through promotion tools only. A channel can provide sampling of the product also with the help of promotion tools (e.g. trailers/promos on the channel or its website). This background has led the investigator to study the promotion preferences of Indore and Dehradun audiences for Hindi and English news channels. A set of 500 viewers from both the cities (250 each) participated in the study. The viewer response to advertisements, tickers (in general and for various types), and awards has been analysed. The preferences of both sets of audiences are compared and similarities/differences have been presented. The findings of the study have revealed that promotion related aspects play a key role in influencing audience preferences. Based on the findings various recommendations have been made to news channels so as to improve viewership by understanding the audience likings and tastes.